Study on Mask Usage as an Effort to Prevent COVID-19 in Public Area (Case Study on Visitors of Oebobo Bus Terminal in Kupang City) - Modesta Riani Manis; Ribka Limbu; Helga Ndun (Lontar : Journal of Community Health, 2022)
The use of masks is part of a series of comprehensive precautions to minimize the transmission of COVID-19. The use of shows aims to protect healthy people when in contact with an infected person and control the source to prevent further information. The use of masks in preventing COVID-19 is listed in health protocols, including keeping a distance (at least 2 meters) and washing hands using soap. This study aims to see an overview of the use of masks to prevent COVID-19 in public places based on the predisposition factor and actions of visitors at the Oebobo Bus Terminal in Kupang City. The research informant consisted of 9 people, including eight key informants, namely the driver and passenger of the bus, and one supporting informant, namely terminal employees. The informant was selected using purposive sampling techniques. This study uses descriptive qualitative methods. The results showed that informants have good knowledge regarding masks in preventing COVID-19. Meanwhile, the attitude of informants in responding to the recommendations of using masks varies; some respond positively, some with negative attitudes; this is due to the informant's lack of belief in the risk of transmission of COVID-19. For using masks, the results showed that most informants had applied well to each component of the action. The government should be active in understanding the importance of COVID-19 prevention so that informant attitudes can change positively